Urban External Economies and Optimal Migration - Vibhooti Shukla; Oded Stark (Migration, Human Capital and Development, 1986)
In this paper we utilize urban economics to identify socially optimal levels of urbanization and, by implication, optimal levels of rural-to-urban migration. Our analysis addresses, first, the case where there is only one urban center (region) in the economy and, second, where there are two. Since in this latter case inter-urban migration flows are possible as well, we examine the rationale underlying dispersal from the larger urban center to the smaller one. After identifying the reason that private actions do not add up to the social optimum, we offer an analysis of instruments that could confer efficiency gains by closing the gap(s) between the privately efficient and socially optimal urban concentrations.
Keywords: 330